Usefulness of combined ultrasonography and MRI to distinguish the diagnosis of Adenoid Cystic Carcinoma of the floor of the mouth - Antigoni Delantoni; Sarafopoulos Apostolos; Zisis V.; Anagnostou Eleftherios; Vachtsevanos Konstantinos; Paraskevopoulos Konstantinos; Andreadis Dimitrios (Balkan Stomatological Society, 2024)
Background/Aim: Adenoid cystic carcinoma (ACC) is a rare type of cancer that most often occurs in the salivary glands. The aim of this report was to describe a very rare case of ACC in the floor of the mouth referring to the usefulness of combined imaging methodology for the detection of the exact origin and extension of the tumor. Case Report: A 70-year-old female patient was referred to the private practice of one of the authors (D.A., Thessaloniki, Greece). Before the examination, the patient provided written informed consent in accordance with the Helsinki Declaration for research and patient's ethics. Subsequently, the patient was examined thoroughly. She exhibited a swelling on the floor of the mouth (left side). The swelling was painless, firm-solid upon palpation, non-movable and attached to adjacent tissues with normal covering oral mucosa. The patient was referred for an ultrasonography and MRI examination and afterwards an incisional biopsy was performed. The surgical removal of ACC and the involved sublingual but also the adjacent submandibular (for safety reasons) salivary glands were performed under general nasopharyngeal anesthesia with bilateral, both external and intraoral access. In addition, post-surgical radiotherapy was performed. Conclusions: Due to the aggressiveness of the lesion and the fact that in most cases adjacent tissues are affected, surgeons tend to be rather aggressive in their interventions. The imaging techniques may vary in their interpretation of the lesions. Ultrasonography and MRI examinations may assist the surgeon by depicting borders of the lesion under investigation, much more accurately, supporting the establishment of the diagnosis and avoiding the unnecessary loss of healthy neighboring tissue.